Zwierzęta czyste i nieczyste w Starym Testamencie. Porządek stworzenia jako kryterium podziału - Majewski, Marcin (Collectanea Theologica, 2019)
The article explicates the symbolic information in the biblical division of animals between clean and unclean (Lev 11 and Dt 14). This is the third article in the series. In the first article on the subject of unclean animals in the Bible, I dealt with the discussion of legislation in this field. In the second article I presented and analyzed the exegetes’ previous interpretations regarding the division of animals in the Bible. Because they proved to be unsatisfactory to me, in this part I proposed my own hypothesis: the exclusion of unclean animals is regulated by the Priestly (P) theology of creation and the rules of the universe created by God contained in Gen 1.